STUDI EVALUASI DAN PERENCANAAN SISTEM JARINGAN DRAINASE KECAMATAN ROGOJAMPI KABUPATEN BANYUWANGI - Muamar Khadafi; Ernawan Setyono (Department of Civil Engineering, Faculty of Engineering, University of Muhammadiyah Malang, 2014)
STUDI EVALUASI DAN PERENCANAAN SISTEM JARINGANDRAINASE KECAMATAN ROGOJAMPI KABUPATENBANYUWANGIMuamar Khadafi1, Ernawan Setyono21&2Jurusan Teknik Sipil Fakultas Teknik – Universitas Muhammadiyah MalangAlamat korespondensi : Jalan Raya Tlogomas 246 Malang 65144ABSTRACTParts of the eastern part of the island of Java there is a district in the district called banyuwangi.The condition of the existing drainage system in the sub-district Rogojampi banyuwangi can say isinadequate to accommodate the construction of both the discharge flow from the waste comesfrom household or storm water discharge exists as hydrological impacts that occur in the regiontersabut. As a result, many districts Rogojampi often encounter serious problems due to standingwater is often the case in several sections of the area especially during the rainy season arrives. Soit is important to evaluate the channel capacity and planning of the new drainage system.Based on the evaluation results can be known that there are several sections of the channelwere not able to hold back the flood discharge stage biennial (two-year Q), so that the necessary replanningthe channel cross section. It provides a new drainage plan is also required to reduce thepool of water when it rains. It also required some supporting buildings culvert drainage system tominimize area genagnanKey Word ; Drainage, Discharge, Normalisation, Planing, Evaluasition